Saturday allied health services for geriatric evaluation and management: A controlled before‐and‐after trial. (9th May 2019) - Taylor, Nicholas F.; Lawler, Katherine; Brusco, Natasha K.; Peiris, Casey L.; Harding, Katherine E.; Scroggie, Grant D.; Boyd, Jude N.; Wilton, Anita M.; Coker, Freya; Ferraro, John G.; Shields, Nora
Abstract: Objective: To assess the effect of Saturday allied health services on a geriatric evaluation and management ward. Methods: A controlled before‐and‐after trial at two wards. Allied health services were added to usual weekday staffing on Saturdays for 6 months on the experimental ward. Length of stay, functional independence, readmissions, discharge destination and costs were evaluated at pre‐intervention (N = 331) and intervention (N = 462). Results: Relative to the comparison ward, the experimental ward had longer length of stay (mean 7.8 days, 95% CI 4.7‐10.8), fewer readmissions (mean 3.1 days, 95% CI 0.6‐5.7) and no difference in the proportion discharged home. Cost‐effectiveness demonstrated no significant difference in cost ($2639, 95% CI $‐386 to $5647) and functional independence gain (3.6 units, 95% CI 0.8‐6.5) favouring the experimental ward. Conclusion: These findings do not support the provision of additional Saturday allied health services in geriatric evaluation and management to reduce length of stay.